Răspuns :
Răspuns:
[tex]\boldsymbol{ \red{ S = \{4;3\} }}[/tex]
Explicație pas cu pas:
Aducem la numitor comun:
[tex]\begin{cases}3x + 2(x + y) = 26 \\ 3(x - y) = 2y - 3\end{cases} \Rightarrow \begin{cases}3x + 2x + 2y = 26 \\ 3x - 3y = 2y - 3\end{cases} \Rightarrow \begin{cases}5x + 2y = 26 \ \ \big|\cdot3 \\ 3x - 5y = - 3 \ \ \big|\cdot(-5) \end{cases}[/tex]
[tex]\Rightarrow \begin{cases}15x + 6y = 78 \\ -15x + 25y = 15\end{cases}[/tex]
[tex]31y = 93 \Rightarrow y = 3[/tex]
[tex]5x+6=26 \Rightarrow 5x = 20 \Rightarrow x = 4[/tex]
Soluția este
S = {4; 3}